High Power‐ and Energy‐Density Supercapacitors through the Chlorine Respiration Mechanism. (7th December 2022) - Fan, Xiaotong; Huang, Kai; Chen, Long; You, Haipeng; Yao, Menglei; Jiang, Hao; Zhang, Ling; Lian, Cheng; Gao, Xiangwen; Li, Chunzhong
Abstract: Supercapacitor represents an important electrical energy storage technology with high‐power performance and superior cyclability. However, currently commercialized supercapacitors still suffer limited energy densities. Here we report an unprecedentedly respiring supercapacitor with chlorine gas iteratively re‐inspires in porous carbon materials, that improves the energy density by orders of magnitude. Both electrochemical results and theoretical calculations show that porous carbon with pore size around 3 nm delivers the best chlorine evolution and adsorption performance. The respiring supercapacitor with multi‐wall carbon nanotube as the cathode and NaTi2 (PO4 )3 as the anode can store specific energy of 33 Wh kg −1 with negligible capacity loss over 30 000 cycles. The energy density can be further improved to 53 Wh kg −1 by replacing NaTi2 (PO4 )3 with zinc anode. Furthermore, thanks to the extraordinary reaction kinetics of chlorine gas, this respiring supercapacitor performs an extremely high‐power density of 50 000 W kg −1 . Abstract : We report an unprecedentedly high power‐ and energy‐density supercapacitor through the chlorine respiration in porous carbon materials. Both electrochemical results and theoretical calculations show that porous carbon with pore size around 3 nm delivers the best chlorine evolution and adsorption performance.